Weight optimization of 200 mm diameter rocket motor tube using finite element method - Wibawa, Lasinta Ari Nendra; Daryana, Alit; Saparudin, Parid; Indrayana, Wan Dedy Fitrah; Handriyana, Handriyana; Diana, Asep; Sobirin, Toris (Politeknik Negeri Lhokseumawe, 2023)
The lightweight design of the rocket motor tube is a critical requirement for enhancing the rocket's flight performance. This study assesses the impact of wall thickness, cap thickness, and fillet radius on structural strength and the optimization of rocket motor tube weight using the finite element method with the assistance of Ansys software. A total of 12 finite element model variations, utilizing Aluminium 6061-T6, were developed and subjected to a uniform internal operating pressure load of 10 MPa. The design includes wall thickness variations of 8 and 10 mm, cap thickness options of 25 and 30 mm, and fillet radius dimensions of 20, 25, and 30 mm, allowing for a comprehensive comparison to achieve the required minimum safety factor while minimizing structural weight. The research concludes that increasing the fillet radius is a more recommended approach compared to increasing wall thickness and cap thickness. The results indicate that Model 9, with wall thickness, cap thickness, and fillet radius dimensions of 10 mm, 25 mm, and 30 mm, respectively, is the optimal choice due to its lightweight construction.